EVALUATION OF ROAD ROUGHNESS AND ROAD DETERIOATION - Djakfar, Ludfi; Prabowo, Gigih Adi; Wicaksono, Achmad; Rahmawati, Vita Dwi (Jurnal Transportasi, 2013)
There are two road condition survey methods commonly used, the roughness-based equipment such as NAASRA and the distress and severity type road evaluation method as presented by ASTM D-6433. The objective of the study is to evaluate the relationship between road condition obtained from roughness type equipment and road distress. To achieve the objective, a condition survey using the two methods were performed on two road segments in the East Java Provincial road system. Data obtained from the field was evaluated to obtain International Roughness Index (from NAASRA) and Present Condition Index value (from field condition survey). The results show that the two methods provide a comparable result when the distress type is of un-even surface such as rutting and bumping. A slight different result is observed when the major distress occurred in the road is of crack-type such as fatigue and block cracking.